Impact of Thrombus Burden in Patients with Acute Coronary Syndrome during the Hospital Stay: A Cross-Sectional Study at a Tertiary Center in Nepal - Bhusal, Khem Raj; Gajurel, Prof Ratna Mani (Journal of Institute of Medicine Nepal, 2025)
Introduction Acute coronary syndrome (ACS) is the leading cardiovascular (CV) cause of mortality and necessitates prompt diagnosis and treatment. Luminal thrombus secondary to coronary plaque rupture is considered as the underlying mechanism for ACS. Intracoronary thrombus burden was a strong predictor for adverse outcomes including stent thrombosis, myocardial re-infarction, and mortality. Methods This study was done in consecutively taken 72 patients presenting with acute coronary syndrome. Angiographic grading of intracoronary thrombus was done according to TIMI thrombus grading. Information on Cardiovascular risk factors and comorbidities was obtained and analysis was done with respect to Thrombus Grade. Adverse cardiovascular outcomes during hospital stay, length of hospital stay and in-hospital mortality were analyzed with respect to thrombus grade. Results Among 72 patients studied, the mean age was 58.93 (± 14.22 years) ranging from 30 years to 91 years. Males were 36.1% while 63.9% were females. Regarding the comorbidities, 62.5% were Hypertensive, 34.7% were Diabetic, 6.9% had hypothyroidism, 2.8% had chronic kidney disease and 5.6% had chronic obstructive pulmonary diseas, 38.9% were active smokers, 15.3% were former smokers, 34.7% were alcohol consumer, 5.6% were tobacco consumer and 1.4% were substance abuser. Among the participants, 6.9% had prior history of MI and 4.2% had prior history of stroke. High thrombus burden was associated with longer duration of hospital stay (p-value=0.026). Conclusion High Thrombus burden was significantly associated with longer duration of hospital stay because of being sicker due to higher cardiovascular events in high thrombus group. Cardiovascular complications were significantly higher in high thrombus burden group.